O nowym odczytaniu Floriana Znanieckiego. Otwarcie debaty nad książką Uroszczenia i transaktualność w humanistyce. Florian Znaniecki: dziedzictwo idei i jego pęknięcia na posiedzeniu Towarzystwa im. Floriana Znanieckiego - Witkowski, Lech (Chowanna, 2023)
The text is a transcription of the author’s presentation discussing theses of his book Uroszczenia i transaktualność w humanistyce. Florian Znaniecki: dziedzictwo idei i jego pęknięcia (Impuls, Cracow 2022). The author emphasizes the polemic character of his conclusions as confronted with the Polish reception of Znaniecki among sociologists, pedagogists, philosophers and psychologists.